2015
DOI: 10.2308/bria-51090
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Professional Role, Decision Context, and Gender on the Ethical Decision Making of Public Accounting Professionals

Abstract: This study investigates the degree to which professional role (auditor or tax professional), decision context (an audit or tax environment), and gender influence the ethical decision making of public accounting professionals. The primary analysis, including all 134 accounting professionals who participated in our experiment, indicates that these participants are both less likely to indicate they would concede to a client in a contentious situation and less likely to recommend conceding when they are in an audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 63 publications
2
30
0
2
Order By: Relevance
“…This argument is in line with current research showing that auditors with higher client identification are more likely to make concessions to clients' preferences (Bamber & Iyer, ; Herda & Lavelle, ; Svanberg & Öhman, ). Finally, Bobek, Hageman, and Radtke () showed that the influence of the professional role on the evaluation of a contentious issue is greater for male participants than for female participants. Following this line of argumentation, our gender effect may also be explained by the male participants reacting more defensively than their female counterparts when confronted with ambiguity and possible impediments to auditor independence.…”
Section: Resultsmentioning
confidence: 99%
“…This argument is in line with current research showing that auditors with higher client identification are more likely to make concessions to clients' preferences (Bamber & Iyer, ; Herda & Lavelle, ; Svanberg & Öhman, ). Finally, Bobek, Hageman, and Radtke () showed that the influence of the professional role on the evaluation of a contentious issue is greater for male participants than for female participants. Following this line of argumentation, our gender effect may also be explained by the male participants reacting more defensively than their female counterparts when confronted with ambiguity and possible impediments to auditor independence.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond these studies focusing on auditors' unprofessional behaviour, the merits of this approach are also justified by an extensive literature in psychology (moral reasoning) (Kohlberg, ; Gilligan, ), business ethics (Ford & Richardson, ; Robin & Babin, ; Borkowski & Ugras, ; Loe, Ferrell & Mansfield, ; O'Fallon & Butterfield, ; Craft, ) and accounting (Ponemon & Gabhart, ; Jones et al , ; Curtis, Conover & Chui, ; Bobek, Hageman & Radtke, ), examining the effect of gender on individual ethical behaviour. In spite of the abundance of empirical studies, our review of the literature on this topic shows that results remain somewhat mixed and inconclusive.…”
Section: Gender and Auditors' Un(ethical) Behaviourmentioning
confidence: 99%
“…In the accounting field, numerous studies have also investigated the effect of gender on accounting professionals' ethical behaviour (Ponemon & Gabhart, ; Jones et al , ; Curtis et al , ; Bobek et al , ). They produce the same mixed and inconclusive results as those observed in the business field.…”
Section: Gender and Auditors' Un(ethical) Behaviourmentioning
confidence: 99%
“…The results drawing on Forsyth classification indicate that individuals with a more relativistic ideology could make more lenient decisions than could individuals with a more idealistic ideology. In this vein, Bobek et al (2015) find In contrast, few studies that have examined professional accountants did not find any of the ethical ideologies to be significantly different from the others in terms of their ethical judgments (e.g., Marques and Azevedo-Pereira, 2009). Douglas et al (2001) showed that ethical ideology is a significant determinant of ethical judgments only in situations of high moral intensity.…”
Section: Ethical Ideology: Effects On Moral Development and Ethical Bmentioning
confidence: 74%